2022
DOI: 10.3390/app12031548
|View full text |Cite
|
Sign up to set email alerts
|

Design of Titanium Alloy Femoral Stem Cellular Structure for Stress Shielding and Stem Stability: Computational Analysis

Abstract: The main objective of this study is to design titanium alloy femoral stems with cubic porous structures that will be able to reduce stress shielding and promote stem stability. These porous structure designs were introduced into titanium alloy femoral stems as homogeneous and functionally graded porous structures. First, the cubic cellular structures were simulated under compressive loading to measure the yield and modulus of elasticity for various porosity ranges. Based on the selected porosity range, fifteen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 48 publications
(84 reference statements)
1
30
0
Order By: Relevance
“…Hence, major factors -including the potting material and fixation orientation of the stems -were controlled, in order to ensure the validity of all comparative analyses performed during this study. The stiffness value of the porous stem (2.15 kN/mm) was comparable (0.42-2.18 kN/mm) to the previous developed porous hip stems in the literature (Harrysson et al, 2008;Mehboob et al, 2020b;Tan and van Arkel, 2021;Al Zoubi et al, 2022).…”
Section: Stem Stiffnesssupporting
confidence: 78%
“…Hence, major factors -including the potting material and fixation orientation of the stems -were controlled, in order to ensure the validity of all comparative analyses performed during this study. The stiffness value of the porous stem (2.15 kN/mm) was comparable (0.42-2.18 kN/mm) to the previous developed porous hip stems in the literature (Harrysson et al, 2008;Mehboob et al, 2020b;Tan and van Arkel, 2021;Al Zoubi et al, 2022).…”
Section: Stem Stiffnesssupporting
confidence: 78%
“…In contrast, Hedia et al (2019) compared the influence of porosity in their study but also material grading with a porosity decrease toward the distal end and reported a stress increase in the femur [ 48 ]. Al Zoubi et al (2022) compared radially graded and uniform designs with different porosities and found that designs with increasing porosity toward the center of the implant performed best in terms of stress transfer to bone, but also micromotion and mechanical strength [ 28 ]. Singh et al (2018) reported that a combination of both, radial and axial grading, could further enhance the decrease in stress shielding and the increase in bone ingrowth [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the multi-axial, dynamic, and high loading conditions at joints, the requirements of joint replacements differ from other bone-interfacing implants such as those for the treatment of large bone defects. Additionally, other factors besides stress shielding affecting implant longevity, including wear [ 54 , 70 ] and micromotion [ 14 , 15 , 28 , 35 , 44 , 46 , 50 , 59 61 , 63 , 70 , 84 ], were not considered in the analyses.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the stem structure, using a slotted or grooved design or hollow and porous structures can reduce the local stiffness of the stem by reducing the material volume, which can increase the load transmitted to the bone [ 5 ]. Although such designs have been shown to reduce SS [ 4 , [6] , [7] , [8] , [9] , [10] ], several studies found that the stress on the femur after implantation is still less than on the intact femur, especially around the proximal lateral side near the greater trochanter [ 6 , 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%